Mechanical properties and microstructural evaluation of the heat-affected zone in ultra-high strength steels. (December 2020) - Amraei, Mohsen; Afkhami, Shahriar; Javaheri, Vahid; Larkiola, Jari; Skriko, Tuomas; Björk, Timo; Zhao, Xiao-Ling
Abstract: This paper presents an investigation into the mechanical properties of ultra-high strength steels (UHSSs) (with nominal yield stress of 960 and 1100 MPa) after welding. Seven weld thermal cycles were simulated using a Gleeble 3800 thermal-mechanical machine. These cycles represented the temperature-time history of the joint at various distances from the weld fusion line (FL) in a typical gas metal arc welding (GMAW) process. The mechanical properties such as Vickers surface hardness, uniaxial tensile behavior and Charpy impact toughness were examined. Microstructural evaluation using field emission scanning electron microscopy (FESEM) was also conducted. According to the results, the S960 which was a direct-quenched type of steel, showed a considerable reduction in its hardness and tensile strength up to 29 and 32%, respectively. On the other hand, the S1100 which was manufactured via quenched and tempered process, showed only a minor degree of softening at far distances from the weld FL (up to 4%) followed by 2% tensile strength reduction, and hardening close to the FL (up to 13%). Microstructure analysis has been carried out to provide insight to the change of mechanical properties in UHSS after welding. Highlights: Conducted tensile tests on CFRP-strengthened butt-welded ultra-high strength steel (UHSS). Performed FE analysis of CFRP-strengthened butt-welded UHSS under tension. Compared with results of CFRP-strengthened mild steel under tension. Compared with results with high frequency mechanical impact treatment and TIG-dressing.